2015
DOI: 10.1002/2015ja021016
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry of subauroral ion drifts: Statistical results

Abstract: A large database of more than 18,000 subauroral ion drift (SAID) events from DMSP observations from 1987 to 2012 is used to systematically investigate the features of SAID. SAID occurs mostly at ~62°/−60° magnetic latitude (MLAT) and ~22:15/22:45 magnetic local time (MLT) for geomagnetically quiet conditions and at ~58°/−56° MLAT and ~22:15/22:45 MLT for geomagnetically disturbed conditions in the North Hemisphere (NH)/South Hemisphere (SH), respectively. Significant north‐south asymmetries in SAID occurrence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…Until now, although many modeling studies (e.g., Goldstein et al, , Lyatsky et al, , Wang et al, ) and observations (e.g., Clausen et al, , Foster & Vo, , Oksavik et al, ) regarding the dynamics of SAPS have been reported in the literature, some key questions are still not fully addressed, such as what is the relationship between SAPS and storms/substorms and what is the role of interplanetary magnetic field (IMF) in the generation and evolution of SAPS. Zhang et al () also found that the location of the SAID peak velocity is a linear function of Kp , Dst , AE , and SYM‐H indices but with hemispheric asymmetry. Karlsson et al () showed that the maximum strength of the subauroral electric fields had a dependence on the y component of the IMF (IMF B Y ) in both hemispheres.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Until now, although many modeling studies (e.g., Goldstein et al, , Lyatsky et al, , Wang et al, ) and observations (e.g., Clausen et al, , Foster & Vo, , Oksavik et al, ) regarding the dynamics of SAPS have been reported in the literature, some key questions are still not fully addressed, such as what is the relationship between SAPS and storms/substorms and what is the role of interplanetary magnetic field (IMF) in the generation and evolution of SAPS. Zhang et al () also found that the location of the SAID peak velocity is a linear function of Kp , Dst , AE , and SYM‐H indices but with hemispheric asymmetry. Karlsson et al () showed that the maximum strength of the subauroral electric fields had a dependence on the y component of the IMF (IMF B Y ) in both hemispheres.…”
Section: Introductionmentioning
confidence: 94%
“…Subauroral polarization streams (SAPS) refer to narrow channels of strong westward ion flows (poleward electric fields) in both the subauroral ionosphere and the conjugated inner magnetosphere during geomagnetic storms and substorms (Foster & Burke, 2002). The term subauroral ion drifts (SAIDs) are usually used to describe the localized very intense westward ion flow (>1 km/s) within the SAPS and often appear as a spike in the flow speed with a latitudinal width of 1°-2° (Anderson et al, 1993(Anderson et al, , 2001Karlsson et al, 1998;He et al, 2014;Zhang et al, 2015). Anderson et al (1993) and Karlsson et al (1998) proposed that SAID typically occur during the substorm recovery phase (RP), while Figueiredo et al (2004) found that they show first an increase in speed and a decrease in latitudinal width during the expansion phase, followed by weakening in intensity and widening of the structures during the RP.…”
Section: Introductionmentioning
confidence: 99%
“…The SAPS channel exhibited a significant hemispheric asymmetry in velocity, width, and latitudinal location as shown by “06:50:17 N15,” “07:03:46S12,” and “07:01:29S14” in 2000–2200 MLT sector in Figure e, with the SAPS in the SH ~6° more equatorward in MLAT than those in the NH and stronger. Possible reasons causing such an asymmetry are the following: An effect of the MLT of observations given that there were differences of about 1–2 hr MLT between the NH and SH crossings, although the difference of SAPS in MLAT is generally less than 2° in a 1‐hr MLT sector according to the statistical results of Foster and Vo () and Zhang et al (). Hemispheric asymmetry of the auroral oval (see the diamonds on the “07:03:46S12” and “06:50:17 N15” orbits in Figure c). Strong stretching of the geomagnetic field lines on the nightside caused by the large tail currents (Skoug et al, ) and the penetration of strong IMF B Y into the closed nightside inner magnetosphere (Reistad et al, ). Hemispheric difference of ionospheric Pedersen conductivity. The ionospheric total Pedersen conductivity (Σ P ) is expressed as ΣP=ΣPP2+ΣPS2, where the precipitation‐produced conductivity (Σ PP ) is calculated with Robinson's relationship (Robinson et al, ) based on the DMSP observations of particle precipitation and the solar‐produced conductivity (Σ PS ) that is obtained with the Rich model (Zhang et al, ).…”
Section: Observationsmentioning
confidence: 99%
“…The latitudinal profile of drift velocity is similar to a single peak Gaussian function. SAIDs happen mostly near ~60° magnetic latitude (MLAT) and ~2200 magnetic local time (MLT), and with a full width at half maximum (FWHM) between 0.05° and 2.0° [ Karlsson et al ., ; Figueiredo et al ., ; He et al ., ]. High correlations between the MLATs of SAIDs and the downward region 2 field‐aligned currents (R2‐FACs) and between the FWHM of SAIDs and the density of R2‐FACs [ He et al . ] indicate that R2‐FACs play an important role in the generation and evolution of SAIDs. The occurrence, shape, and geomagnetic activity variations of SAIDs have a significant north‐south asymmetry [ Zhang et al ., ].…”
Section: Introductionmentioning
confidence: 99%